2017
DOI: 10.1017/s1047951117002542
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of switch from bosentan to macitentan in children and young adults with pulmonary arterial hypertension

Abstract: Our study is the first study that showed that switch from bosentan to macitentan significantly improved exercise capacity in children and young adults with pulmonary arterial hypertension and is well tolerated without any adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…Currently there is only limited experience on the use of macitentan in children. Available data include one smaller study in children older than 12 years 17 and a recently published work by Flores et al. 18 reporting on their initial experience of macitentan in two smaller children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently there is only limited experience on the use of macitentan in children. Available data include one smaller study in children older than 12 years 17 and a recently published work by Flores et al. 18 reporting on their initial experience of macitentan in two smaller children.…”
Section: Discussionmentioning
confidence: 99%
“…1315 Whereas clinical trials and case reports in adults support its efficacy and tolerability, data on children are limited. 1618,2127…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Кроме того, среди трех зарегистрированных в настоящее время АРЭ бозентан обладает наибольшим гепатотоксическим потенциалом, из-за которого препарат не может рассматриваться в качестве препарата первого ряда для пациентов с недавно диагностированной ЛАГ. Напротив, новый неселективный тканеспецифичный препарат мацитентан в дозе 10 мг не только подтвердил свою эффектив-ность у больных ЛАГ в качестве монотерапии, но и в комбинации с силденафилом [15]. Препарат обладает хорошим спектром безопасности и не имеет ранее описанных для этого класса препаратов гепатотоксических эффектов или клинически значимых лекарственных взаимодей ствий.…”
Section: Discussionunclassified
“…17,18 We have recently reported that switch from bosentan to macitentan significantly improved exercise capacity in children and young adults with pulmonary arterial hypertension in a 24-week prospective study and well tolerated without adverse events. 19 We now aimed to evaluate clinical efficacy, safety of switch from bosentan to macitentan in a larger patient population and in a 24-month prospective study due to desirable features (once-a-day profile and freedom from monthly liver function tests) of macitentan.…”
mentioning
confidence: 99%